Load Factor Analysis of KMP Bambit Pioneer Ship to Enhance Maritime Accessibility in Eastern Indonesia's 3T Regions - Rusnaedi Rusnaedi; Andi Ningrat; Muslihati Muslihati; Andi Rachmianty; Rifkah Fitriah (Politeknik Siber Cerdika Internasional, 2026)
Background: As the world's largest archipelagic nation, Indonesia faces the major challenge of providing an equal distribution of public services to 3 not so close and remote frontier region, border (3T) regions. An example: While the government's Sea Toll Program uses pioneer vessels such as KMP Bambit to breach these chasms, efficiency of operation is still a major barrier to progress. This often results in underused capacity Objective: This study aims to analyze the load factor of KMP Bambit on the Merauke-Atsy-Agats-Senggo route and identify strategic recommendations to improve ship capacity utilization and service quality And see if there is a reasonable load factor on KMP Bambit operating from the Merauke-Atsy-Agats-Senggo route. Depending on this finding, strategic advice is put forward with regard to vessel capacity utilisation and service quality. Method: This investigation used quantitative research. Throughout the research period from January 2022 to June 2025, data were collected on operational ship activities and survey results were sought from 65 stakeholders according to the Slovin Formula. The data were analyzed using Load Factor Analysis (LF A) and a SWOT analysis was performed to map internal and external strategic factors. Results: Our findings show that the average load factor for passengers is 42.427% and the cargo/vehicle load factor is 45.141%, both significantly below the Ministry of Transportation's 70% efficiency target. Problems include inconsistent sailing frequencies, limited port infrastructure, and changing seasonal demand levels. Conclusion: Being in Quadrant I of SWOT Matrix, KMP Bambit needs to take a growth-oriented strategy. Major recommendations are to modernize ship facilities, implement an online reservation system, and adjust sailing schedules in line with community needs in order to bring sustainable economic growth south to the remote regions of South Papua it serves.